Neurodegenerative disease: expression levels of normal sequence pathogenic proteins contribute to risk of disease - Hardy, John (Henry Stewart Talks, 2007)
Protein pathology of disease, Loci underlying autosomal dominant neurodegenerative disease, Prion mutations causing Gerstmann Straussler syndrome and hereditary Creuzfeldt-Jakob disease, Tau mutations cause autosomal dominant frontal temporal dementia, Alpha-synuclein mutations cause autosomal dominant Parkinson's disease, How genetic variability of these genes contributes to the risk of sporadic disease
Updated at 2021/03/08